Comparison of Stromal Vascular Fraction with or Without a Novel Bioscaffold to Fibrin Glue in a Porcine Model of Mechanically Induced Anorectal Fistula. Issue 11 (November 2017) - Dryden, Gerald W.; Boland, Eugene; Yajnik, Vijay; Williams, Stuart
Abstract : Background: Anorectal fistulas (ARFs) are a common, devastating, event in the life of a patient with Crohn's disease. ARFs occur in up to 50% of patients with Crohn's disease. Treatment begins with surgical drainage of the initial abscess, followed by antibiotic therapy, then anti-inflammatory medications. If medical therapy fails to close the fistula tract, surgical intervention is often pursued. Surgery incurs risk of incontinence because of sphincter injury. Increasingly, the role of cell-based therapy is being investigated in ARFs. We evaluated the role a bioabsorbable scaffold plays in delivering cell-based therapy using a porcine model of AFR. Methods: ARFs were mechanically created and matured by setons. After 28 days, setons were removed; periaortic fat was harvested and processed for stromal vascular fraction (SVF). The cells were labeled with a membrane stain for later identification, then injected into the fistula or implanted through scaffold. Fistulas not treated with cells were injected with fibrin glue. Animals were monitored visually for healing at weeks 2 and 4, then euthanized to evaluate fistulas for histologic healing. Results: All fistulas (6/6) treated with SVF + scaffolds healed by week 2, compared with only 4/6 with just SVF and 0/5 treated with fibrin glue. Scaffolds retained SVF within the fistula tract more readily than injection method and SVF+scaffold treatment accelerated the healing process. Robust neovascularization was also seen in fistulas treated with SVF+scaffold. No adverse events occurred. Conclusions: Scaffold technology may improve cell-based therapy healing rates for Crohn's ARFs. This advance should be investigated by human trials. Abstract : Article first published online 22 September 2017.